Mesoscale mechanisms of larval transport and settlement in relation to physical factors off the south coast of South Africa: a topographic approach - Mian, Shana Iva (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2016)
The majority of benthic marine invertebrate life cycles include a meroplanktonic phase. Most marine biologists recognise that this stage could play an important role in dispersal, especially for sedentary or sessile organisms. Recent studies on larval dispersal have found that dispersal does not occur to the extent that was previously believed. Some larvae instead remain close to their natal populations through larval nearshore retention mechanisms, both active and passive. This study attempted to a) describe nearshore distribution patterns of several intertidal larvae in relation to nearshore hydrodynamics, b) infer whether larvae are active or passive in the water column and whether this differs among taxa and c) compare pelagic mussel larval abundance with settlement rates, at 2 bay and 2 open coast sites on the south coast of South Africa to note any topographical effects. At each of the four sites, pelagic samples were collected along 2 transects. Larvae and current speed data were collected at various depths (surface, mid-depth and bottom) at distances of 200, 400, 900 and 2400m offshore of the coast. Settlement samples were collected at sites that were onshore of the pelagic transects using plastic souring pads following previous studies. Pelagic larval distribution showed no effect of topography. Instead larval abundance was highly variable among sample periods and among different taxa. Slow swimming D-stage mussel larvae were found to be positively correlated with both upwelling and turbulence indices suggesting that they behave as passive particles in the water column. The abundances of larval taxa with faster swimming speeds than the D-larvae were negatively correlated with upwelling and did not correlate with turbulence. This suggests that these larvae are more active within the water column than the D-larvae which would theoretically allow them to maintain their position in the water column. Further analysis revealed that mean larval depth correlated with mean depth of shoreward moving water masses regardless of the state of upwelling. These results suggest that larvae were actively selecting the depth at which they were found presumably in order to associate themselves with shoreward moving currents. This interpretation was supported by ontogenetic patterns in the behaviour of barnacle larvae, the nauplii of which were found further offshore as they aged, and closer onshore again once they reach the faster swimming cyprid stage. Although there was no detectable effect of topography on the abundances of planktonic larvae, the settlement section of this study revealed an effect of topography, with higher settlement and recruitment rates at bay sites than at the open coast sites. Settlement rates were seen to be negatively correlated with turbulence at bay sites but not open coast sites. Recruitment rates for each sample event were positively correlated with upwelling at each site. This study found pelagic larvae to be generally active within the water column which allowed them to remain close to the shore regardless of topography and upwelling/turbulence regimes. Although meaningful correlation analyses between pelagic larval supply and settlement rates could not be conducted due to loss of settlement collectors, settlement rates were affected by local topography with higher settlement and recruitment in bay sites.
Keywords: Uncatalogued